"una empresa docente": a teaching enterprise (1999)
"Una empresa docente" is a research center in Mathematics Education of the University of los Andes, in Bogotá, Colombia. It was created ten years ago, and it is now part of Science Faculty of the University. Its mission is to support the process of improvement of the teaching and learning of school mathematics in the country through the empowerment of the Colombian system of Mathematics Education. This process of empowerment is envisaged as a process of change of the different actors involved in the process: teachers, administrators and institutions, through the implementation of reflexive innovations at the curriculum level. In order to attain this mission, "una empresa docente" has four main strategic areas of work: curriculum innovation, research, teacher training and infrastructure development.